2022
DOI: 10.1177/01430343221091201
|View full text |Cite
|
Sign up to set email alerts
|

Exploring self-care experiences of school counsellors: A qualitative study

Abstract: School counsellors are responsible for maintaining their well-being to provide quality service for the students. Self-care activities are the best way to preserve and enhance the well-being of counsellors. In this vein, this study aimed to discover the self-care experiences of school counsellors employing a qualitative approach. Fifteen licensed school counsellors (eight of whom were female) from various schools in Turkey participated in the study. Data were gathered through semi-structured interviews. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(95 reference statements)
1
4
0
Order By: Relevance
“…Although participants mostly discussed personal self-care activities (Lee & Miller, 2013), three participants also described the need to set boundaries between work and home. As found in other studies (e.g., Şimşir Gökalp, 2022), our participants stated that often their workday did not end at a certain time, and they needed to set firmer boundaries for themselves. Establishing such work-life balance is a professional self-care strategy that these participants learned to develop over time.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Although participants mostly discussed personal self-care activities (Lee & Miller, 2013), three participants also described the need to set boundaries between work and home. As found in other studies (e.g., Şimşir Gökalp, 2022), our participants stated that often their workday did not end at a certain time, and they needed to set firmer boundaries for themselves. Establishing such work-life balance is a professional self-care strategy that these participants learned to develop over time.…”
Section: Discussionsupporting
confidence: 81%
“…Despite creating boundaries between work and home, participants described other barriers to self-care that they have faced. In the literature, barriers to self-care often include administrative and noncounseling duties, role ambiguity, and high workloads (Maor & Hemi, 2021;S ¸ims ¸ir Gökalp, 2022). Participants in this study experienced similar barriers, which often corresponded with the top five concerns that the ASCA (2021) study revealed, such as the need to lower the student-to-school-counselor ratio, ensuring that administrators understand the school counselor's role, responding to student crises, and addressing school policies that have marginalized certain populations of students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that school counselors in Türkiye do not act on personal agency to shape their work environment, overcome problems, and build their well-being, and they do not engage in proactive behaviors. However, Şimşir Gökalp (2022) found that some Turkish school counselors participate in activities to foster their WSE, such as professional development courses, to prevent burnout and cope with barriers. Furthermore, these school counselors stated that as their professional self-efficacy increased, they were better engaged in work-related tasks and problems and their well-being was fostered (Şimşir Gökalp, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, Şimşir Gökalp (2022) found that some Turkish school counselors participate in activities to foster their WSE, such as professional development courses, to prevent burnout and cope with barriers. Furthermore, these school counselors stated that as their professional self-efficacy increased, they were better engaged in work-related tasks and problems and their well-being was fostered (Şimşir Gökalp, 2022). Similarly, recent studies noted that counselor self-efficacy of Turkish school counselors promotes their job satisfaction (Ak & Deniz Yöndem, 2022; Aydın & Odacı, 2020).…”
Section: Introductionmentioning
confidence: 99%